MOLECULAR IDENTIFICATION OF FOOD-BORNE PATHOGENIC ESCHERICHIA COLI FROM MARINE FISHES - RWARINDA U ANGELO,; SAMIRAJ RAMESH, (International Journal of Pharma and Bio Sciences, 2017)
The collection and identification of bacterial isolates are paramount for the correct diagnosis and from different food-borne diseases. The methods of bacterial identification relied on phenotypic tests, which are often time-consuming and unreliable when identifying atypical strains. Traditional methods could be done and followed by a molecular approach which is fast and reliable for the identification of isolates, this could be achieved by comparing a 16S ribosomal RNA gene sequence with publicly available sequences. In the present study, isolated bacteria were characterized and its DNA was extracted and amplified by PCR using universal primers, and then a partial 16S rRNA gene sequence was obtained and compared with sequences deposited in public DNA sequence databases; EMBL/GeneBank and DDBJ. Bacterial isolates belonging to Escherichia coli species as identified by culturing methods, biochemical tests as well partial 16S rRNA gene sequence to the species level. We conclude that the identification of bacteria with partial 16S rRNA gene sequence is an efficient and specific tool complement to phenotypic identification.